Problem Based Learning dalam Mengembangkan Kemampuan Berpikir Kritis Siswa Sekolah Dasar - Maulana El-Yunusi, Muhammad Yusron; Novita Sari (Program Studi Tadris Ilmu Pengetahuan Sosial (TIPS) UIN Datokarama Palu, 2023)
This research aims to determine and analyze students' critical thinking skills that are developed in Islamic religious education subjects at SD Negeri 28 Gresik. The focus of this research is on the application of the Problem Based Learning model in developing students' critical thinking skills in Islamic Religious Education subjects and the supporting and inhibiting factors. This type of research is qualitative using a naturalistic approach. The research location was carried out at SD Negeri 28 Gresik. Data collection techniques use observation methods, in-depth interviews, and documentation. Data analysis techniques use data reduction, data presentation, and triangulation. This research produced the following findings: First, the critical thinking abilities that are formed in SDN 28 Gresik students in PAI subjects can be seen from the following competencies: a. able to formulate the main problems in a material; b. able to express facts to solve problems; c. able to choose logical, relevant, and accurate arguments; d. able to provide opinions from various points of view; e. able to resolve problems arising from a statement. Second, the application of the Problem-Based Learning model to develop students' critical thinking skills in Islamic religious education subjects at SD Negeri 28 Gresik is carried out through the following activity program: a. student orientation to the problem; b. organizing students to study; c. guiding student investigations; d. presenting student work; e. analyzing and evaluating the problem-solving process. The third finding regarding supporting and inhibiting factors for implementing the Problem Based Learning model to develop students' critical thinking skills in Islamic religious education subjects is as follows, a. The supporting factors are school leadership factors, teacher factors, student factors, and school facility factors, b. The factors that become obstacles are that the learning process is less conducive and time is limited.